Violence and unsafety in a major Italian hospital: experience and perceptions of health care workers - Terzoni, Stefano; Ferrara, Paolo; Cornelli, Roberto; Ricci, C.; Oggioni, Chiara; Destrebecq, Anne (La Medicina del Lavoro, 2015)
Workers’ experience of violence and perceived unsafety can have a profound impact on job satisfaction, job performance, and workers’ decision to leave. Objectives: The aim of the study was to assess the prevalence of physical and non-physical violence among hospital workers, explore the complaints and reactions of victims, assess the relationship between violence and psychosocial/work factors and analyze the levels of perceived unsafety. Methods: A cross-sectional study was conducted, via a structured self-administered questionnaire given to all the employees of a major hospital in Italy. Cronbach’s alpha coefficient was used to assess the internal consistency of the questionnaire. A logistic regression model was used for data analysis. Results: 903 questionnaires out of 1853 (48.7%) were correctly returned; 11.5% had experience of physical violence and 40.2% had been victims of verbal violence in the previous 12 months. The most common consequences were fear, anger, frustration, and anxiety. Verbal violence was influenced by age, role, department, night/holiday shift work and experience in the current ward. Experiences of physical violence were related to gender, role, and department; 469 responders (51.9%) reported feelings of unsafety, which were related to their professional role, department, shift work, experience of physical or psychological violence, having seen episodes of violence and having received specific training. Conclusions: Our findings suggest that several factors are associated with workplace violence in health care settings and some of these also influenced the levels of perceived unsafety.